Pengaruh Gender, Tingkat Pendidikan dan Pengetahuan Perpajakan Terhadap Wajib Pajak Orang Pribadi - Maria Juvianti Mayorga; Suyanto, Suyanto (RELASI : JURNAL EKONOMI, 2024)
This study aims to prove the influence of Gender, Education Level andKnowledge of Taxation on individual Taxpayer Compliance (Case Study ofindividual taxpayers in Yogyakarta. This research is a quantitative study. Thesample of this research is individual taxpayers registered at the KKP PratamaYogyakarta. The sample was selected by purposive sampling method with certaincriteria. The total sample is 257 respondents. Data analysis was carried out byvalidity and reliability tests, classical assumption tests and multiple linearregression analysis with SPSS 26.The results of this study indicate that Gender,Education Level and Tax Knowledge have a positive effect on individual taxpayercompliance.Keywords: Gender, Education Level, Tax Knowledge, Taxpayer Compliance